Molecular detection of HPV 16/18 E6 genes from cervical cells - Auwal, Idris Kabuga; Rogo, Lawal Dahiru (International Journal of Research in Medical Sciences, 2017)
Background: Epidemiological, clinical and molecular studies have established the link between genital infection with high risk human papillomavirus (HPV) and cervical cancer but there is great challenge in establishing early infection by both clinicians and the laboratories. The virus cannot be grown in conventional cell cultures and serology cannot different between active and past infection. Molecular studies remain the goal standard as it detects viral nucleic acid or cellular antigens indicative of oncogenic potential in cytology or biopsy specimen. The study was aimed to molecularly determine the presence of HPV 16/18 and expression of E6 gene in squamous intraepithelial lesions. Methods: Cervical cells were collected from 18 women with positive cytology test results and 32 controls in gynaecology clinic of Murtala Muhammad Specialist Hospital, Kano Nigeria and HPV 16/18 were detected with E6 gene specific PCR primers. Results: Overall, HPV E6gene was found in 76% of the women, 88.3% of positive cytology specimens and 71.2% controls. Conclusions: There is very high prevalence of HPV infection. The presence of HPV 16/18 E6genes in cervical intraepithelial lesions may serve as a useful predictor of diagnosis and possible clinical outcome of the disease.